DEVELOPMENT OF CO-TRANSLATIONAL CAS9 PROTEIN EXPRESSION SYSTEM WITH UPSTREAM CHAPERONE IN BI-CISTRONIC SYSTEM - Patisenah, Alfred
The CRISPR/Cas9 system is a molecular biology technique that has revolutionized genetic and molecular biology research. CRISPR/Cas9 must be able to enter the nucleus of the target cell to function. The transfection method of delivering functional ribonucleoprotein complexes into the target cell is preferred in several fields due to its speed, accuracy, and transgene-free nature. However, producing recombinant Cas9 protein remains challenging as Cas9 protein is prone to form inactive inclusion bodies. Molecular chaperone engineering systems have been used to enhance recombinant protein production in soluble forms. In this study, a co-translational chaperone-based strategy, chaperone-substrate colocalized expression (CLEX), was implemented to increase the solubility of Cas9 protein expressed in Escherichia coli. This system combined the expression of the DnaJ co-chaperone and Cas9 protein using a 5?-TAATG-3? overlapping start-stop codon in a bicistronic system, effectively spatially restricting bacterial molecular chaperones to the Cas9 translation site. The study comprised several stages, including the design and construction of the Cas9 CLEX expression plasmid, Cas9 solubility test, and Cas9 activity test. The genetic constructs of this expression system were assembled using overlap-extension PCR and integrated into the pRSFDuet-1 expression vector by restriction cloning. In this study, a genetic construct of the DnaJ gene located upstream of Cas9 was successfully generated. Cas9 expression was carried out using Escherichia coli BL21(DE3) as the host, and the protein solubilization effect was evaluated by performing SDS-PAGE on soluble and insoluble protein fraction samples. The tested expression conditions included variations in temperature and expression duration. The results indicated that the Cas9 CLEX system may impose an excessive metabolic burden on the host cells, resulting in lower Cas9 yield and solubility levels. On the other hand, expression at a low temperature (18°C) positively influenced the yield and solubilization of Cas9 with both the CLEX and non-CLEX systems. Cas9 produced using the CLEX system was purified through Ni-NTA affinity column chromatography and ultrafiltration. The endonuclease activity of Cas9 was tested using sgRNA targeting the dsDNA substrate of the eIF4E1 gene and analyzed by agarose gel electrophoresis. The yield of pure Cas9 using the CLEX system was 0.463 mg per 100 mL of culture, which was 2.3 times lower than the control. However, Cas9 produced with CLEX exhibited normal endonuclease activity. In general, based on this study, the CLEX system with upstream DnaJ works better at a temperature of 18°C for the production of large-sized proteins.